Effectiveness of Cognitive Behavioral Therapy Techniques on Anxiety and Depression in Cancer Patients - Cem Soylu (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Depression and anxiety are generally considered to be the most important psychopathological comorbidities of cancer patients and experienced by approximately one-third of cancer patients. In the literature, studies have reported that patient characteristics such as gender, age, education level and disease characteristics such as recurrence, stage of cancer and metestazis are associated with anxiety and depression among cancer patients. Cognitive Behavioral Therapy (CBT) and techniques are one of the most frequently used approach in studying the effects of psychological intervention on anxiety and depression in cancer patients and its value has been demonstrated in reducing distress with diverse cancer populations. The aim of cognitive-behavioral interventions is to change particular thoughts and behaviors and teach specific coping skills, such as cognitive restructuring, behavior modification, relaxation training and activity plan by using specific techniques. Cognitive restructing, stress management and desensitization, relaxation and activity scheduling with use of diary sheet are most used among CBT techniques. This review summarizes the diagnosis, prevalence, risk factors and treatment of depression and anxiety in patients with cancer and CBT techniques applied to these symptoms and study findings related to treatment. [JCBPR 2015; 4(1.000): 54-63]